2001
DOI: 10.1002/jpp.334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric and low molecular weight phthalocyanines from nitriles and metal carbonyls on SiO2 and TiO2 and catalytic activities in the sulfide oxidation

Abstract: ABSTRACT:A new method for coatings of polymeric phthalocyanines and for comparison also of low molecular weight phthalocyanine metal complexes (W, Cr, Mo, Co) on quartz and titanium dioxide was developed by the reaction of metal carbonyls adsorbed on the carriers with tetracarbonitriles or phthalonitrile. By UV-vis or IR spectra the formation of structural uniform polymeric phthalocyanines on the carriers is established. The compounds are used then to compare their catalytic and photocatalytic activities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Many studies have already reported in this respect. [25][26][27][28][29][30][31] However, in our best knowledge, no report in photo-decomposition of dipropyl sulfide using solid embedded metal-phthalocyanines or triphenylpyrylium ion has been reported till now in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already reported in this respect. [25][26][27][28][29][30][31] However, in our best knowledge, no report in photo-decomposition of dipropyl sulfide using solid embedded metal-phthalocyanines or triphenylpyrylium ion has been reported till now in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Various photosensitizers, such as dyes, porphyrines and phthalocyanines, have been used to be photosensitizers to oxidize thiols, sulfide, thioethers, phenol and monochlorophenols [22][23][24][25][26] Recently, polynuclear metal phthalocyanine complexes have attracted attentions because of their increased catalytic properties compared to mononuclear one [27,28]. Some polynuclear cobalt phthalocyanine complexes exhibit a much higher specific activity to activate the oxygen than the mononuclear compound in the oxidation of sulfide [29]. As the photocatalyst in the photooxidation of sulfide, thiosulfate, and phenol, the catalytic activity per mole of the polynuclear zinc and aluminium complexes is two to five times higher than that of the respective mononuclear phthalocyanine complexes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sulfur-containing compounds, such as mercaptans, alkali sulfides, alkali sulfites and alkali thiosulfates are byproducts of industrial processes and these are the persistent pollutants of waste and natural waters [21,22]. The complete oxidation of sulfur-containing compounds (using metal oxide and semiconductor oxide), before discharging them into waterways, was suggested to be a possible solution for environmental pollution problems [23][24][25][26]. As an alternative to inorganic semiconductors, metallophthalocyanines (MPcs) were used to produce photocatalytic systems [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%